Radioimmunoassay of circulating LH during oestrous cycles of Surti buffaloes - NIGAM, R; PATHAK, M; MEHTA, V M (The Indian Journal of Animal Sciences, 2013)
A sensitive and reproducible radioimmunoassay from buffalo serum was standardized using heterogenous system. The assay sensitivity was 0.17 ng/tube. Intra and interÂ·assay coefficients of variation for the system were 6 and 11 % respectively. The peak level ofLH before ovulation averaged to 9.68Â±2.83 ng/ml for cycling Surti buffaloes. The basal level ranged between 1.01 and 2.26 ng/ml throughout the rest of cycle.